Alpha1-adrenergic receptor blockade in the ventral tegmental area attenuates acquisition of cocaine-induced pavlovian associative learning - Solecki, Wojciech B.; Kielbinski, Michał; Bernacka, Joanna; Gralec, Katarzyna; Klasa, Adam; Pradel, Kamil; Rojek-Sito, Karolina; Przewłocki, Ryszard (Frontiers in Behavioral Neuroscience, 2022)
Activity of the alpha1-adrenergic receptor (α1-AR) in the ventral tegmental area (VTA) modulates dopaminergic activity, implying its modulatory role in the behavioral functions of the dopamine (DA) system. Indeed, intra-VTA α1-AR blockade attenuates conditioned stimulus dependent behaviors such as drug seeking responses signifying a role of the noradrenergic signaling in the VTA in conditioned behaviors. Importantly, the role of the VTA α1-AR activity in Pavlovian associative learning with positive outcomes remains unknown. Here, we aimed to examine how intra-VTA α1-AR blockade affects acquisition of cocaine-induced Pavlovian associative learning in the conditioned place preference paradigm (CPP). The impact of α1-AR blockade on cocaine-reinforced operant responding and cocaine-evoked ultrasonic vocalizations (USVs) was also studied. In addition, both α1-AR immunoreactivity in the VTA and its role in phasic DA release in the nucleus accumbens (NAc) were assessed. We demonstrated cellular localization of α1-AR expression in the VTA, providing a neuroanatomical substrate for the α1-AR mechanism. We showed that prazosin (α1-AR selective antagonist; 1 µg/0.5 µl) microinfusion attenuated electrically-evoked DA transients in the NAc and dose-dependently (0.1-1 µg/0.5 µl) prevented the acquisition of cocaine CPP but did not affect cocaine-reinforced operant responding nor cocaine-induced positive affective state (measured as USVs). We propose that the VTA α1-AR signaling is necessary for the acquisition of Pavlovian associative learning with positive outcome. Thus, α1-AR signaling in the VTA might underlie salience encoding of environmental stimuli and reflect an ability of alerting/orienting functions, originating from bottom-up information processing to guide behaviors.